Comparative Study of Friction Stir Welding and TIG Welding of Aluminum (6061) Alloy - Sapkota, Ritesh; Chhantyal, Bikki; Maharjan, Sanjeev (Journal of Advanced College of Engineering and Management, 2024)
Friction stir welding (FSW) has shown promising outcome in joining thermoplastics, Aluminum, surpassing traditional methods. This experimental study compares the welding of Aluminum 6061 material by Friction Stir Welding and TIG welding. The weld of aluminum plates of 6 mm thickness is obtained by FSW and TIG Welding. The microstructure analysis of weld is done using optical microscope and mechanical properties of weld is obtained using UTM. The tensile strength of the Aluminum weld using FSW is higher compared to the TIG welding. The welding strength regained is nearly 41.3% by the FSW and 15.6% by TIG welding. Coarse grain is obtained at the weld nugget in the FSW and finer grain is obtained in case of TIG Welding. Weld is less brittle in FSW than TIG Welding as the % elongation is 3.24 in FSW and 0.76 in TIG welding.